Analysis of Short-circuit Fault in DC Traction Power Supply System for Urban Mass Transit - 王乃永; 艾兵; 李静; 曹晖; 吴广宁 (Kongzhi Yu Xinxi Jishu)
Fault analysis of DC traction power supply system plays an important role in programming and designing, equipment choice, scheme protection and debugging of the whole urban mass transit. The whole power grid may be influenced badly if the metro DC power supply system suffers short-circuit fault. It presents a model of rectifier and DC system for metro traction power supply system based on Matlab/ Simulink , analyzes the operation characteristic of the rectifier, researches dynamic response of the close short-circuit and the distant shortcircuit fault for DC power supply system, which provides a valuable reference for the design optimization, parameter setting and system debugging.